FRENCH IMMIGRATION POLICY DURING THE COVID-19 PANDEMIC - Yao Xuedan (Journal of Liberty and International Affairs, 2022)
Following the start of the European refugee crisis in 2015, France had to modify its immigration and asylum policies. However, France faced two main issues resulting from the pandemic: pandemic control and refugee management. This article examined the reform and adjustment of France's immigration and refugee asylum policies before and after the pandemic outbreak. It concluded that the pandemic had aggravated the problems of refugee management in France. At the same time, refugees in France were in a difficult situation. The French government had imposed restrictions on entry and exit, leaving many refugees stranded in France, unable to return home. Moreover, the high sanitary conditions of accommodation due to the pandemic led to the fact that the health of many refugees could not be guaranteed. Therefore, the French government should enhance the guarantee of a healthy environment for refugees, which is also beneficial to the social management of France.